Servicio de recolección selectiva de residuos sólidos municipales y el nivel de satisfacción en usuarios - Yurimaguas 2022 - Terrones Vásquez, Yeltsin Richelly (2024)
The proper management of municipal solid waste is decisive due to its environmental impact. In Yurimaguas, a Program of Source Segregation and Selective Collection of Municipal Solid Waste was implemented to promote sustainable waste management practices. However, it is necessary to understand user satisfaction and its relationship with service quality. The objective of this study was to establish the relationship between the quality of the service Program of Source Segregation and Selective Collection of Municipal Solid Waste and the level of user satisfaction in Yurimaguas. Non- experimental, correlational, cross-sectional and quantitative research. The sample consisted of 109 heads of households in the program. Non- probabilistic unique sampling was used. A questionnaire with a Likert scale was applied, with a Cronbach's coefficient greater than 0.89 for both variables. The majority reported high satisfaction with operational quality and customer service. 99% had a "high" level in these areas. Security, awareness and environmental responsibility received high ratings, with 100% at the "high" level. 95% showed high satisfaction with the service. There was no relationship between satisfaction and quality perceptions. Satisfaction may have been influenced by various factors. It is recommended to continue improving operations and customer service through training and evaluations. Further analysis of satisfaction in safety and environmental responsibility is suggested, as well as considering other influential factors.